m6A Regulator-Mediated RNA Methylation Modification Patterns are Involved in the Pathogenesis and Immune Microenvironment of Depression - Wang, Ye; Wang, Xinyi; Yang, Chenyi; Hua, Wei; Wang, Haiyun (Frontiers in Genetics, 2022)
Depression is a genetically susceptible disease characterized by neuroinflammatory symptoms and is difficult to diagnose and treat effectively. A recent technique, modification of N 6-methyladenosine (m6A) at the gene level, is closely related to immune regulation. Therefore, the purpose of this study was to explore the effect of m6A modifications on the occurrence of depression and on the composition of the immune microenvironment. We used the Gene Expression Omnibus (GEO) to download gene expression profiling data of healthy and depressed rats. We described the overall expression of the m6A regulator in animal models of depression and then constructed risk and clinical prediction models through training and validation sets. We performed bioinformatics analysis using gene ontology (GO) functions, gene set enrichment analysis, gene set variation analysis, weighted gene co-expression network analysis, and protein-protein interaction (PPI) networks. We used the CIBERSORT to identify immune-infiltrating cells in depression and perform a correlation analysis. We then constructed two molecular subtypes of depression and assessed the correlation between key genes and molecular subtypes. Through differential gene analysis of m6A regulators in depressed rats, we found 7 m6A regulators that were significantly upregulated in depressed rats and successfully constructed a clinical prediction model. GO functional annotation showed that the m6A regulators enriched differentially expressed genes in biological processes, such as the regulation of mRNA metabolic processes. Further, 12 HUB genes were selected from the PPI network. Immune cell infiltration analysis showed that levels of inflammatory cells, such as CD4 T cells, were significantly increased in depressed rats and were significantly correlated with the depression HUB genes. Depression was divided into two subtypes, and the correlation between hub genes and these two subtypes was clarified. This study outlines the effect of m6A modification on the pathogenesis of depression, with a particular emphasis on the role of inflammatory infiltration.